Acoustic disturbance in blue mussels: sound-induced valve closure varies with pulse train speed but does not affect phytoplankton clearance rate. (28th October 2022) - Hubert, Jeroen; Moens, Rosalie; Witbaard, Rob; Slabbekoorn, Hans
Abstract: Anthropogenic sound has increasingly become part of the marine soundscape and may negatively affect animals across all taxa. Invertebrates, including bivalves, received limited attention even though they make up a significant part of the marine biomass and are very important for higher trophic levels. Behavioural studies are critical to evaluate individual and potentially population-level impacts of noise and can be used to compare the effects of different sounds. In the current study, we examined the effect of impulsive sounds with different pulse rates on the valve gape behaviour and phytoplankton clearance rate of blue mussels ( Mytilus spp.). We monitored the mussels' valve gape using an electromagnetic valve gape monitor and their clearance rate using spectrophotometry of phytoplankton densities in the water. We found that the mussels' valve gape was positively correlated with their clearance rate, but the sound exposure did not significantly affect the clearance rate or reduce the valve gape of the mussels. They did close their valves upon the onset of a pulse train, but the majority of the individuals recovered to pre-exposure valve gape levels during the exposure. Individuals that were exposed to faster pulse trains returned to their baseline valve gape faster. Our results show that different sound exposures can affect animals differently, which should be taken into account for noise pollution impact assessments and mitigation measures.